“To die is better than to tell”: reasons for and against disclosure of chronic hepatitis B status in Ghana - Adjei, Charles Ampong (BMC Public Health, 2020)
BACKGROUND: People with a condition subject to stigmatisation, such as chronic hepatitis B, face the dilemma of whether or not to disclose their status. In Ghana, 12.3% of the adult population has the hepatitis B virus (HBV). One key strategy for breaking the cycle of hepatitis B transmission is the disclosure of hepatitis B status by people with chronic hepatitis B (PWHB). Disclosure can facilitate preventive actions to reduce hepatitis B transmission (e.g., not sharing personal items and avoiding contact with blood and body fluids). Disclosure can also motivate family members of PWHB to get tested, linked to care and clinically managed in order to reduce the progression of hepatitis B to liver cirrhosis and cancer. Given the importance of disclosure, we set out to explore reasons for and against disclosure of chronic hepatitis B status in the Greater Accra and Upper East region of Ghana. METHODS: In this exploratory qualitative study, 18 participants (10 from the Greater Accra region and 8 from the Upper East region) were recruited for semi-structured interviews. Interviews were recorded and transcribed verbatim. Data were then processed using QSR Nvivo version 10.0 and analysed for themes. RESULTS: Participants were selective disclosers, disclosing in some contexts and not in others. Reasons for non-disclosure of chronic hepatitis B status were: 1) fear of stigmatisation and 2) previous negative experiences with disclosure. Reasons for disclosure were: 1) wanting close contacts to get tested or vaccinated, 2) trusting the disclosure target(s), and 3) needing social and/or financial support. CONCLUSIONS: Our findings highlight various reasons for and against disclosure of chronic hepatitis B status in Ghana. Because anticipated, observed, and experienced stigma were important motivations for non-disclosure of chronic hepatitis B status, we recommend the development and implementation of theory and evidence-based stigma reduction interventions that are culturally appropriate, and that prioritize the participation of target populations. We also recommend the provision of counselling and support services that assist PWHB in their disclosure decision-making processes.